The influence of geographic origin and food type on the susceptibility of Callosobruchus maculatus (Fabricius) to Piper guineense (Schum and Thonn). (July 2015) - Oyeniyi, Emmanuel A.; Gbaye, Olajire A.; Holloway, Graham J.
Abstract: The tolerance of Callosobruchus maculatus from different geographical locations reared on two cowpea varieties, pale brown Ife Brown (IFBV) and dark brown IAR48 (IAR48V), to seed powder of Piper guineense (Schum and Thonn) was investigated. C . maculatus populations were collected from nine different locations across Osun state in the South Western part of Nigeria. The main and interactive effects of cowpea variety, population origin and dose on C . maculatus tolerance to P . guineense were explored. It was observed that bruchids that emerged from IAR48V had greater tolerance of P . guineense than bruchids reared on IFBV. There were significant effects (P < 0.001) of cowpea variety, population and dose, and significant interactions among these factors (except variety × dose, P > 0.05) on the response of bruchids to P . guineense . When reared on IAR48V, bruchid populations from the North-Eastern part of the state show greater tolerance to P . guineense than their counterparts from the South–West. This study underscores the importance of knowledge of the origin of the population and the cowpea variety on which C . maculatus developed when managing bruchids damage using P . guineense . Highlights: Impact of cowpea variety on response of Callosobruchus maculatus populations to Piper guineense was studied. Variety had a significant effect on bruchid response to botanical pesticide. Bruchid origin and cowpea variety interaction impacted highly on bruchid tolerance. There was no significant interaction of variety and dose on response.